2023
DOI: 10.3390/agronomy13102528
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fruit Maturity and Quality of ‘Buckeye Gala’ Grown on a Diverse Panel of Apple (Malus domestica Borkh.) Rootstocks in Western Maryland

Md Shipon Miah,
Chloe Hinson,
Macarena Farcuh

Abstract: Apple (Malus domestica Borkh.) is usually produced in the form of a rootstock grafted scion. Rootstocks have important effects on several horticultural attributes. However, the results are not consistent regarding sites and scion–rootstock combinations. The aim of this research was to characterize the horticultural performance of ‘Buckeye Gala’ apple scion grafted onto ten rootstocks grown in Western Maryland during two harvest seasons. Our results demonstrated that, on average, tree size and yield in G.935, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…The internal ethylene concentration (IEC) of each fruit was measured on 1 mL samples of internal gas from the core cavity using a gas chromatograph (GC-2014C, Shimadzu Co., Kyoto, Japan) equipped with an activated alumina column attached to a flame ionization detector as previously described [28,45,46]. Nitrogen (N 2 ) was used as the carrier gas at a flow rate of 30 mL min −1 , while O 2 and H 2 were used to create the flame of the detector at a flow rate of 300 and 30 mL min −1 , respectively.…”
Section: Fruit Internal Ethylene Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal ethylene concentration (IEC) of each fruit was measured on 1 mL samples of internal gas from the core cavity using a gas chromatograph (GC-2014C, Shimadzu Co., Kyoto, Japan) equipped with an activated alumina column attached to a flame ionization detector as previously described [28,45,46]. Nitrogen (N 2 ) was used as the carrier gas at a flow rate of 30 mL min −1 , while O 2 and H 2 were used to create the flame of the detector at a flow rate of 300 and 30 mL min −1 , respectively.…”
Section: Fruit Internal Ethylene Concentrationmentioning
confidence: 99%
“…Fruit quality is determined by multiple irreversible physiological and biochemical modifications that take place as fruit matures [26]. These include modifications in fruit skin color (background and red surface color), texture (flesh softening), and flavor (increase in sugar contents, decrease in organic acids, and changes in aroma volatiles) [27][28][29]. In addition, regarding preharvest fruit drop, ethylene can promote the degradation of the cell wall and intercellular tissues in the abscission zone of the pedicel, resulting in fruit drop [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit internal ethylene concentration (IEC) was measured using 1 mL samples of internal gas from the core cavity of each fruit using a gas chromatograph (GC-2014C, Shimadzu Co., Kyoto, Japan), as described before [ 4 , 50 , 82 ]. The apple fruit red skin coloration was assessed as previously described [ 4 , 50 , 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the initiation of anthocyanin biosynthesis and ethylene production concur [ 48 ]. However, ethylene production can also enhance fruit ripening, therefore directly impacting the fruit quality [ 4 , 49 , 50 , 51 , 52 , 53 ], and, at the same time, can promote the apple preharvest fruit drop [ 54 ]. The biosynthesis of ethylene has been significantly studied in fruit that present a climacteric behavior, such as apples, which display a rise in their rate of respiration and the internal ethylene concentration (IEC) as the ripening progresses [ 50 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation